ANALISIS EKONOMI USAHA PENGOLAHAN NUGGET UDANG DI UD. KAYA RASA KECAMATAN SAMARINDA SEBERANG KOTA SAMARINDA - Pujiono; Erwiantono; Erwan Sulistianto (2339-1324, 2017)
This study aims to determine the basic financial criterias of business feasibility based on indicators Revenue Cost Ratio (RCR), break event or Break Event Point (BEP) and marketing channels of shrimp nugget processing business, at UD. Kaya Rasa, Keledang Mas Baru Resident, Sub District of Samarinda Seberang, Samarinda. This research was conducted during 6 months starting in November 2015 until April 2016. The data was collected by interviewing the informant. The study designed using the case study method and the sampling is done by using census method. Analysing of the data used the basic finance criterias of business feasibility and then presented in tabular form. The results showed that the shrimp nugget processing business was profitable and feasible, showed by the results of Revenue Cost Ratio (RCR) were 1,194, Break Event Point (BEP) in sales were Rp.9.015.949/month, Break Event Point (BEP) in prices were Rp.12.565/packaging, Break event point (BEP) in production were 679/month. The margins on marketing agencies were Rp.3.000/pack, or equal to of 83,34%.